PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN PENGGUNAAN DAN PERSEPSI RISIKO TERHADAP MINAT BELI KONSUMEN PADA TIKTOK SHOP DI SIDOARJO - Silvy Imelda Windari; Rizky Eka Febriansah; Dewi Komala sari (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to determine the influence of Perceived Usefulness, Perceived Ease of Use, and Perceived Risk on Consumer Purchase Intention at TikTok Shop in Sidoarjo. This research method uses a quantitative approach. The population in this study is all Sidoarjo residents who use TikTok. The sampling technique used a non-probability method with a purposive sampling approach, with a sample size of 100 respondents. The data collection method was carried out by distributing online questionnaires via Google Forms, and answers were measured using a Likert scale. The data analysis technique used SPSS software version 22. The results of this study prove that perceived usefulness influences purchase interest, perceived ease of use influences purchase interest, and perceived risk influences purchase interest.